Effectiveness of Cooperative Integrated Reading and Composition (CIRC) Learning Model Based on Local Wisdom to Improve Reading Skills in Children - Ghofur, Abdul; Widiastuti, Rini; Hayati, Noorfah; Doorvina, Doorvina; Sukini, Sukini; Dewanto, Dewanto (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine the effectiveness of the cooperative Integrated Reading and Composition (CIRS) learning model based on local wisdom in improving reading skills in children. This research is a type of meta-analysis research. Research data was obtained from 22 studies that met the inclusion criteria.Â  Data was obtained from Google Scholar, ERIC, ScienceDirect, Wiley, and IEEE databases. Data analysis calculates the effect size value with the help of JASP software. The results of the study concluded that the value of the summary effect size was d = 1.010. These findings show that the cooperative Integrated Reading and Composition (CIRS) learning model based on local wisdom significantly affects reading ability in children with a very high influence category. In addition, this research is expected to contribute to future educational and research practices.